Solidarity cities in Europe: Charity or pathways to citizenship: A new urban policy approach. - (:unkn) unknown (My University, 2019)
There is no such thing as a uniform Solidarity City concept. These differences start with the heterogeneous nature of migrant communities and refugee groups in individual cities, and continue with the question of responsibilities on the municipal level, such as the role of the police or the competences of city governments. Other questions include: what are the possibilities for municipal influence and decision-making? What are the legal conditions for residence and migration? How is access to welfare services regulated? Within Germany, there is no uniform answer to these questions, and the differences are even greater when we compare the various approaches that exist across Europe. Furthermore, there is a lack of empirical studies that examine these differences (and parallels) on an international level. This publication aims to contribute to filling this knowledge and research gap. Our first objective is to incorporate the findings and results of this publication into the debates concerning the development of leftwing migration policy strategies in Germany and Europe. Secondly, we aim to gather the existing approaches and experiences of solidarity cities and present them to the public for discussion. Finally, we seek to include the migrant perspective in the ongoing debates on the municipalist movement and ‘rebel cities’.
Keywords: Stadtgesellschaft; Kommunalpolitik; Zivilgesellschaft; Stadtbewohner; Solidarität; Bürgerbewegung; Einwanderung; Migration; Flüchtling